The Canadian Integrated Multi‐Trophic Aquaculture Network (CIMTAN)—A Network for a New Era of Ecosystem Responsible Aquaculture. Issue 7 (11th July 2013) - Chopin, Thierry; MacDonald, Bruce; Robinson, Shawn; Cross, Stephen; Pearce, Christopher; Knowler, Duncan; Noce, Anthony; Reid, Gregor; Cooper, Andrew; Speare, David; Burridge, Les; Crawford, Curran; et al.
ABSTRACT: The Canadian Integrated Multi‐Trophic Aquaculture Network (CIMTAN) is a Natural Sciences and Engineering Research Council strategic network that was initiated in 2010. It was triggered by the fact that aquaculture, though the world fastest growing food production sector, is associated with environmental, economic, and societal issues. Integrated multi‐trophic aquaculture (IMTA) offers an innovative solution for the environmental sustainability, economic stability, and societal acceptability of aquaculture by taking an ecosystem‐based management approach. IMTA is the farming, in proximity, of aquaculture species from different trophic levels, and with complementary ecosystem functions, so that one species' excess nutrients are recaptured by the other crops and synergistic interactions among species occur. CIMTAN is providing the interdisciplinary research and development and highly qualified personnel training in the following linked areas: (1) ecological design, ecosystem interactions, and biomitigative efficiency; (2) system innovation and engineering; (3) economic viability and societal acceptance; and (4) regulatory science. By mitigating organic and inorganic enrichment of fed aquaculture operations and producing additional extractive crops, IMTA should transform environmental and socioeconomic issues into benefits, trusted quality seafood, and novel seafood‐based products. CIMTAN is going beyond addressing questions of a natural science and engineering nature and is addressing socioeconomic, policy, and regulatory governance components.